STUDY PERENCANAAN STRUKTUR ATAS GEDUNG GUEST HOUSE 6 LANTAI DI KOTA KEDIRI - Ravie Setya Putra; Ahmad Ridwan; Sigit Winarto; Agata Iwan Candra (Kadiri University, 2020)
The increasing number of tourist attractions and airport construction in the city of Kediri will impact the rising number of visitors from outside the city. The availability of adequate accommodation to accommodate the number of visitors who will come to the town of Kediri is essential. Kediri City Guest House Building is one of the solutions to the problem of availability of accommodation in the City of Kediri going forward. Calculations carried out in this study regarding the structure of the 6-story Guest House building design using SAP2000V7.40 software. The results of the standard frame elements in the structure column model with the appropriate dimensions and materials included in the plan drawing. The column section frame has dimensions 600x600 cm and diameter 600 cm. The wall load value is distributed to all frames holding the wall in the form of a uniform load of 250 kg/m2 as planned, the height of the stairs is 2 m, and the length is flat is 2.5 m. Thus, the calculation results obtained the number of stomps of 10 pcs and the number of climbs of 10 pcs with a width of 61cm stairs, aantrade (horizontal) 25 cm, and optrade (up) 20 cm.Â Bertambahnya jumlah tempat Wisata dan pembangunan Bandara di Kota Kediri akan berdampak pada bertambahnya jumlah pengunjung dari luar Kota. Ketersediaan akomodasi yang mencukupi untuk menampung jumlah pengunjung yang akan datang ke Kota Kediri sangat diperlukan. Gedung Guest House Kota Kediri menjadi salah satu solusi pada permasalahan ketersediaan akomodasi kedepannya. perhitungan yang dilakukan Pada penelitian iniÂ Â mengenai perencanaan struktur bangunan Guest House 6 lantai dengan menggunakan software SAP2000V7.40. Hasil elemen frame biasa pada model kolom struktur dengan dimensi dan material yang sesuai telah dicantumkan dalam gambar rencana. Frame section kolom tersebut berdimensi 600 x 600 Cm dan diameter 600 Cm. Nilai beban dinding didistribusikan ke seluruh frame yang menahan dinding dalam bentuk beban merata (uniform load) sebesar 250 kg/m2 seperti rencana tinggi tangga adalah 2 m dan panjang datar adalah 2,5 m. Secara perhitungan diperoleh hasil jumlah injakan 10 bh dan jumlah tanjakan 10 bh dengan lebar tangga 61cm, aantrade (mendatar) 25 cm, dan optrade (naik) 20 cm.